2020
DOI: 10.1017/s1047951120001882
|View full text |Cite
|
Sign up to set email alerts
|

A case of COVID-19 in a patient with a univentricular heart post total cavopulmonary connection (Fontan) surgery

Abstract: Coronavirus disease 2019 (COVID-19) has caused a global pandemic which has affected patients and healthcare systems around the world. Patients with underlying health conditions seem to be more severely affected. There are limited reports of patients with univentricular circulations and COVID 19; thus, we report a case of COVID-19 in a patient with a univentricular circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This is the first reported case, to our knowledge, of an infant with functionally univentricular heart disease and parallel circulation with symptomatic Covid-19. Two previous cases of those with functionally univentricular hearts have been reported although these patients had already undergone Fontan and no longer had parallel circulation [4,5]. There are multiple interesting takeaways from this case.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This is the first reported case, to our knowledge, of an infant with functionally univentricular heart disease and parallel circulation with symptomatic Covid-19. Two previous cases of those with functionally univentricular hearts have been reported although these patients had already undergone Fontan and no longer had parallel circulation [4,5]. There are multiple interesting takeaways from this case.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, some of the children reported to have Covid-19 have been documented to have cardiac disease, but none with functionally univentricular heart disease and parallel circulation (wherein the ascending aortic saturation and pulmonary artery saturations are equal) have been described yet to our knowledge [1][2][3]. Two cases of those with functionally univentricular hearts have been described but these patients had already undergone Fontan palliation and no longer had parallel circulation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…After the exclusion of duplicates, 12 articles were selected for inclusion into the analysis (Fig 1). [11][12][13][14][15][16][17][18][19][20][21][22] These comprised a total of 143 patients, of which 99 had CHDs. The key information from each article is summarised in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of publication, one patient was discharged and the remaining two were still receiving hospital care. 11,13,16 Based on these numbers and outcomes described, it can be seen that patients with underlying CHD are more likely to develop complications than the overall population; however, 82% of patients recovered and were discharged within 10-20 days.…”
Section: Categorymentioning
confidence: 99%
“…At the last follow up point, three patients were discharged and one was still hospitalized. [30][31][32][33] Bezerra et al reported that one female patient was diagnosed with COVID-19 infection after a Fontan procedure for hypoplastic left heart syndrome. Despite the patient was admitted to the ICU and experiencing multiple pulmonary combined with other complications, she was fully recovered and discharged.…”
Section: Overview Of Case Reports In the Literaturementioning
confidence: 99%